VALIDASI METODE UJI SENYAWA CYCLOHEXANE DI UDARA LINGKUNGAN KERJA DENGAN BERBAGAI MODIFIKASI METODE SECARA GAS CHROMATOGRAPHY MASS SPECTROMETRY - Mochamad Rodjulun Kaffah (FT-USNI, 2020)
Determination of the cyclohexane compound used refers to the National Institute of Occupational Safety and Health (NIOSH) method number 1500. Validation of the determination of cyclohexane in air samples of the work environment needs to be done due to modifications between them in different columns, glass columns 3.0 mx 2-mm , 20% SP-2100 on 80/100 mesh Supelcoport becomes Rtx-5MS column, the injector temperature difference, column temperature, detector temperature, and the test material used is cyclohexane pa to cyclohexane for gas chromatography, differences in measurements using FID detectors to spectrometer detectors mass. This experiment aims to ensure the performance of the cyclohexane determination method in the air sample of PT UP's work environment by gas chromatography mass spectrometry (GCMS) in accordance with the accepted method requirements set by PT. Unilab Prime. If all parameters meet the acceptance requirements, then this method can be used for routine analysis. Validation parameters carried out include linearity test, instrument detection limit (LDI), quantitation limit (LK), precision,accuracy, and strength of the method (robustness) using gas spectrometer mass chromatography. Based on the experimental results obtained by the value of the correlation coefficient linearity test (r) of 0.9998,% SBR for the precision test of 1.64%,% recovery obtained range of 89.26% - 105.35%. The instrument detection limit value is 0,0003mg / mL, the quantization limit is 0.0010mg / mL. Testing the strength parameters of the method (Robustness) produces cyclohexane concentrations in accordance with the accepted requirements of the working range of cyclohexane 0.5000mg / mL. Based on the test results obtained the performance of the cyclohexane determination method that has undergone modification in a sample of working air environment by gas chromatography mass spectrometry (GCMS) in accordance with the requirements set by thecompany so that it can be used for routine analysis in the PT Unilab Perdana environmental laboratory.